PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA AUDITOR PADA INSPEKTORAT KOTA KENDARI - Lisnawati, Lisnawati (JURNAL AKUNTANSI, 2016)
This research aimed of presented to examine the effect of emotional intelligence and spiritual intelligence on the performance of Auditors. Primary data in this research were obtained from the perception of all employees involved in the audit process in the scope of the Inspectorate of Kendari. Perceptions of respondents was measured by responses to questionnaires that uses ordinal measurement with a 5 point Likert scale. The analytical tool used to test the hypothesis is multiple linear regression analysis.The result of this research indicate that emotional and spiritual Intelligence partially and simultaneously positively and significant effect on the performance of auditors. The result of the coefficient of determination for emotional and spiritual intelligence is R2 = 0,704. This number can be used to see the contribution of emotional and spiritual intelligence on the performance of auditors is 70,4%, while the remaining 29,6% was obtained from the contribution of other factors.Keywords: Emotional Intelligence, Spiritual Intelligence, and Performance of Auditors.